Academic self-regulated learning and the law student - Macaraan, Maryrose C. (Animo Repository, 2021)
Self-regulated learning explains the behavioral, motivational and cognitive processes involved in the learning experience. The present study discusses the preliminary findings of the initial survey conducted among the DLSU College of Law students who will be taking the 2021 bar exam using the Academic Self-Regulation Scale (A-SRL). The study would use the cyclical framework of self-regulated learning by Zimmerman. The findings show that most of the students strongly agreed to using the forethought or planning strategies but have mixed agreements to the performance or implementation and reflection phases of self-regulation. Program recommendations are included in this paper.